Carbon dioxide laser tissue welding: an alternative technique for tubal anastomosis? - Wallwiener, Diethelm; Meyer, Anke; Bastert, Gunther (Journal of clinical laser medicine & surgery, 1997)
Microsurgical tubal anastomosis is the gold standard for treatment of tubal occlusion. The present study was performed to establish the feasibility of tubal anastomosis by welding tissue with a defocussed CO2-laser beam during laparotomy and with an endoscope. In an animal experiment, 70 white New Zealand rabbits were randomized in 2 study groups (E1, E2) and 3 control groups (C1, C2, C3) as follows: C1, 10 animals, no operation, as controls for the efficiency of the insemination technique; C2,5 animals, spontaneous healing after tubal segment resection, to quantify spontaneous recanalization of the tube; C3, 15 animals, microsurgical end-to-end adaption after tubal segment resection; E1, 20 animals, laser welded anastomosis after segment resection via laparotomy; E2, 20 animals, laparoscopic laser welded anastomosis after segment resection. The pregnancy rate in C1 was 80%. None of the animals in C2 but 60% of the rabbits in C3 conceived. After sutureless anastomosis by laser welding 50% of the laparotomized, and 40% of the laparoscopically operated group became pregnant. Morphological examination of the oviducts after relaparotomy showed comparable patency rates of 70% in C3,70% in E1, and 65% in E2. Whereas no dehiscence of anastomoses was observed in C3,20% of the welded tubes in E1 and 22.5% in E2 were dehiscent. Tubal anastomosis took approximately three times as long laparoscopically as during laparotomy. Thus, laser welding as a sutureless alternative technique of tubal anatomosis should be viewed critically. A reduction of sutures through laser-assisted anastomosis might, however, be considered.